Integrity of CAD/CAM onlays in ceramic and resin composite, associated or not with filler core in vitro study - Queiróz, Camila Thais (2020)
his in vitro study evaluated the integrity of indirect onlay restorations made of leucite-reinforced ceramic (IPS Empress CAD, Ivoclar Vivadent, Schaan, Liechtenstein) and nanoceramic composite resin (LAVA Ultimate, 3M ESPE, São Paulo, Brasil), with and without resin composite filler core (Tetric Ceram, IvoclarVivadent and FiltekZ350 XT, 3M ESPE). Sixty extracted third molars were prepared by planning the occlusal surface with total removal of enamel, until a standard 3mm high crown were obtained. The preparation was performed involving only the distal half of the remaining crown, which was worn with total removal of 2 mm in height of the crown, remaining 1 mm of enamel in the cervical region to make the chamfered end. After standardized preparation, the specimens were divided into four groups: (n=15): Group 1: Leucite-reinforced ceramic onlays without filler core (LC); Group 2: nanoceramic resin composite onlays without filler core (NRC); Group 3: leucite-reinforced ceramic onlays with previous filler core (LC-F) and Group 4: nanoceramic resin composite onlays with previous filler core (NRC-F). In groups 3 and 4 specimens, the filler cores were made with composite resin and over the resin filler core, a standardize preparation was made. All prepared specimens were scanned by a intraoral digital scanner and the ceramic and nanoceramics resin blocks were milled in CAD / CAM to obtain partial crowns that were cemented with Variolink N dual resin cement, (Ivoclar Vivadent, Schaan, Liechtenstein) for ceramics and RelyX Ultimate (3M, ESPE) for nanoceramic resin composite. The specimens were stored in distilled water in an oven at 37 °C throughout the process and at least 24 hours before testing .After cementation, the margins of all restorations were polished and subsequently, all samples were subjected to thermomechanical stress cycling from 5 ° to 55 ° C, simultaneously with compression cycling at different load intensities (100, 200, 300, 400, 450N) in each level 20,000 cycles were performed, totaling 100,000 cycles. At the end of the thermomechanical cycling, the onlays integrity was measured by the presence of cracks and catastrophic fractures, measured by scores. The scores were submitted to statistical analysis Friedman repeated measures test with significance level of =0,05, where no significance were found for both variation factors (material and the presence of filler core), since the survival rate between the groups were similar.